Memory and understanding : concept formation in Proust's A la recherche du temps perdu - Bartsch, Renate, 1939- (Advances in consciousness research, 2005)
This book treats memory and understanding on two levels, on the phenomenological level of experience, on which a theory of dynamic conceptual semantics is built, and on the neuro-connectionist level, which supports the capacities of concept formation, remembering, and understanding. A neuro-connectionist circuit architecture of a constructive memory is developed in which understanding and remembering are modelled in accordance with the constituent structures of a dynamic conceptual semantics. Consciousness emerges by circuit activation between conceptual indicators and episodic indices with th.